Reverse Total Shoulder Arthroplasty - Lenarz, Christopher J. (MyJove Corporation, 2011)
Reverse total shoulder arthroplasty was initially approved for use in rotator cuff arthropathy and well as chronic pseudoparalysis without arthritis in patients who were not appropriate for tendon transfer reconstructions. Traditional surgical options for these patients were limited and functional results were sub-optimal and at times catastrophic. The use of reverse shoulder arthroplasty has been found to effectively restore these patients function and relieve symptoms associated with their disease. The procedure can be done through two approaches, the deltopectoral or the superolateral. Complication rates associated with the use of the prosthesis have ranged from 8-60% with more recent reports trending lower as experienced is gained. Salvage options for a failed reverse shoulder prosthesis are limited and often have significant associated disability. Indications for the use of this prosthesis continue to be evaluated including its use for revision arthroplasty, proximal humeral fracture and tumor. Careful patient selection is essential because of the significant risks associated with the procedure.